Curriculum Centralization Policy Towards the Quality of Learning Madrasah Diniyah Islamic Boarding School Nurul Jadid - Achmad Fawaid; Eka Yanti (Tarbiyah : Jurnal Ilmiah Kependidikan, 2020)
Madrasah Diniyah Nurul Jadid utilize curriculum centralization system. The policy is taken from several evaluations to repair the former system. This research uses qualitative research with phenomenology in Madrasah Diniyah Nurul Jadid, the research result some internal and external effect; first, decreasing santri’s solid time. Second, santri achievement to understand the lesson given is equal. Third, minimizing expense. Fourth, teaching learning process and student or teacher activeness is more monitored. Fifth, able to compete with other Madrasah Diniyah. Sixth, high social loyalty. Seventh, santri guardian or parent can know about personality development of santri in pesantren.